Identity of care in a Psychosocial Care Center for Children and Adolescents who uses drugs - Isabella Teixeira Bastos; Vicente Sarubbi Jr; Tatiane Guimaraes Pedroso de Oliveira; Patricia Santos de Souza Delfini; Camila Junqueira Muylaert; Alberto Olavo Advincula Reis (SciELO, 2014)
Objective To associate the territory of identity with the production of care within a PCC focusing on children and adolescents with drug abuse and their institutional identity. Method We used the " process tracing methodology" in four research categories: focus groups, characterization of professionals, observing the everyday and interviewing two members of emblematic cases of the service. Results territory of identity of the institution, which operates the production of care is crossed by the difficulty of dealing with the complexity brought by the users and the performance of the PCC network. This paper is also permeated by different conceptions of care and small problematization of these issues in collective spaces of service. Conclusion The discussion in focus groups and other devices can be powerful resources to reframe the meaning of care and identity of collective service.